2006
DOI: 10.1177/104063870601800605
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PrPCWD in Postmortem Rectal Lymphoid Tissues in Rocky Mountain Elk (Cervus Elaphus Nelsoni) Infected with Chronic Wasting Disease

Abstract: Abstract. Preclinical diagnostic tests for transmissible spongiform encephalopathies have been described for mule deer (Odocoileus hemionus), using biopsy tissues of palatine tonsil, and for sheep, using lymphoid tissues from palatine tonsil, third eyelid, and rectal mucosa. The utility of examining the rectal mucosal lymphoid tissues to detect chronic wasting disease (CWD) was investigated in Rocky Mountain elk (Cervus elaphus nelsoni), a species for which there is not a live-animal diagnostic test. Postmorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 20 publications
1
54
0
Order By: Relevance
“…In naturallyinfected mule deer, 45 of 50 subclinical and terminal CWD-infected deer, as determined by immunohistochemistry on tonsil or retropharyngeal lymph nodes, were also positive by rectal biopsy [95]. Rectal biopsies to diagnose CWD in elk may also be suitable, as one study showed a strong correlation between tonsil, rectal mucosa, and brain in CWD positive elk, although one of seven elk with early CWD was tonsil positive, but rectal mucosa negative [82].…”
Section: Cwd Diagnosticsmentioning
confidence: 99%
“…In naturallyinfected mule deer, 45 of 50 subclinical and terminal CWD-infected deer, as determined by immunohistochemistry on tonsil or retropharyngeal lymph nodes, were also positive by rectal biopsy [95]. Rectal biopsies to diagnose CWD in elk may also be suitable, as one study showed a strong correlation between tonsil, rectal mucosa, and brain in CWD positive elk, although one of seven elk with early CWD was tonsil positive, but rectal mucosa negative [82].…”
Section: Cwd Diagnosticsmentioning
confidence: 99%
“…A limitation of using lymphoid tissue from the rectal mucosal biopsy technique in elk appears to be a decrease in the number of follicles as elk age. 6,9 If the number of follicles decreases too much, then the test would decrease in sensitivity and be of limited use in older animals. As previously acknowledged, the minimum number of lymphoid follicles needed for an accurate diagnosis of CWD using rectal mucosal biopsies in elk is unknown but is estimated to be 10 follicles.…”
mentioning
confidence: 99%
“…Preclinical diagnostic tests for CWD have been described for mule deer using biopsy tissues of palatine tonsil 10 and rectal mucosa. 13 A rectal mucosal biopsy technique has recently been described 6,9 for detecting CWD in Rocky Mountain elk. Examination of postmortem rectal mucosal tissue sections for evidence of the prion protein associated with CWD (PrP CWD ) has been reported 8 in elk for diagnosis of CWD, and data indicate that the technique may be useful in the diagnosis of preclinical cases of CWD.…”
mentioning
confidence: 99%
“…18,21,24 However, IHC does not routinely detect very early cases of CWD in these tissues. 17,20 Various fluids, such as saliva, blood, urine, and cerebrospinal fluid (CSF) have been evaluated in animals for their use in preclinical antemortem detection of abnormal prions. 4,6,10,22 Due to the minute concentrations of infectious proteins in saliva, blood, and urine, detection of the misfolded infectious prion protein (PrP res ) has been limited or unsuccessful without the use of protein misfolding cyclic amplification (PMCA), which increases the concentration to a detectable level, and is orders of magnitude more sensitive for detecting PrP CWD than commonly used methods such as Western blotting and IHC, 7 enabling detection of minute amounts of infectious prions in animal tissues and environmental samples.…”
mentioning
confidence: 99%